Plan de negocio para la creación de un centro de diversión nocturno evangélico - Aparicio Quinde, Katherine (2009)
Guayaquil has a great variety of clubs and cafes, for all social sectors of the population. An important sector of the population in Guayaquil which is constantly increasing are Christians. Considering these people as a potential market, this project sees the possibility of supply a not yet covered need in the market with a different approach to the rest of places that are currently offering different options of entertainment today in our city. The Christians do not find a place that meets their requirements, some choose to stay in their homes resigned to a non dynamic situation, while others agree to go to bars or restaurants where maybe the music, the cigarette smoke or alcohol, cause them a state of discomfort and dissatisfaction. This project is established on a business model based on customer loyalty. Where the competitive advantage is have a certain power in the negotiation, due to the fact that we are the first business offering a place with this theme. The characteristics it will offer to the customers are live Christian music, music videos, snacks with names attached to Christian doctrine in a fun and youthful way, with characters that would make the customer experience more enjoyable.